KAJIAN METODE ARSITEKTUR BIOKLIMATIK PADA RUMAH ADAT BANJAR GAJAH BALIKU - Farah Hafizha; Sarifah Nur Isra Jairina (Pawon: Jurnal Arsitektur, 2023)
Bioclimatic architecture is a design approach that considers the relationship between architectural forms and the local climate. Vernacular architecture is an architectural design that adapts to the local climate, local construction materials and techniques, influenced by social, cultural and economic aspects of the local community. The ancient architecture of the Gajah Baliku traditional house in South Kalimantan has been around since the 1800s and is part of the vernacular architecture. This study discusses the bioclimatic architectural methods found in the traditional house of Banjar Gajah Baliku. The method used in this study is a qualitative descriptive method which aims to find out how the application of bioclimatic architectural methods to the traditional house of Banjar Gajah Baliku. The data collection method was obtained from primary sources, namely literature which was carried out to find the theoretical basis and become a reference in reviewing empirical data, as well as field observations consisting of measurements, sketches, documentation and redrawing the research object. From this study, it is concluded that the traditional house of Banjar Gajah Baliku in South Kalimantan has met the nine criteria of the bioclimatic architectural method.